A cypovirus encoded microRNA negatively regulates the NF-κB pathway to enhance viral multiplication in Silkworm, Bombyx mori. (June 2022) - Zhao, Ze; Lin, Su; Wu, Wanming; Zhang, Zhendong; Wu, Ping; Shen, Manman; Qian, Heying; Guo, Xijie
Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that function as novel gene expression regulators at the post-transcriptional level. Not with standing that the biogenesis and function of miRNAs are well-understood in eukaryotes, little is known about RNA virus-encoded miRNAs. Bombyx mori cypovirus (BmCPV) is a double-stranded RNA virus with a segmented genome that causes cytoplasmic polyhedrosis disease in silkworm larvae. To date, the interaction between BmCPV and silkworm remains largely unclear. 22 candidate BmCPV-encoded miRNAs were identified in this study through small RNA sequencing, stem-loop RT-PCR and qRT-PCR. Then, generation and function analyses were conducted on one of the candidate miRNAs, BmCPV-miR-1, in the BmN cells and the silkworm larvae by RNA interference, quantitative PCR, dual-luciferase assay. Our results revealed that BmCPV-miR-1 was encoded by BmCPV genome RNA rather than the degraded fragments of the viral genome. Its generation depended on Dicer-1 and might also be correlated with Dicer-2, Argonaute-1 and Argonaute-2. Moreover, BmCPV-miR-1 could suppress the expression of the target gene, B. mori inhibitor of nuclear factor kappa-B kinase subunit beta ( BmIKKβ ), via binding to the target mRNA 3′-untranslated region, which fine-tuned the host NF-κB signaling pathway and consequently enhanced viral replication. Our results provide new evidence supporting the hypothesis that RNA viruses could generate miRNAs to modulate antiviral host defense. Graphical abstract: Image 1 Highlights: At least 22 candidate BmCPV-encoded miRNAs were identified. BmCPV-miR-1 was encoded by BmCPV and its biogenesis depended on Dicer-1. BmCPV-miR-1 suppressed the target gene BmIKKβ by binding to its mRNA 3′-UTR. BmCPV-miR-1 enhanced BmCPV proliferation through suppressing target gene BmIKKβ. Results support the hypothesis that RNA viruses could generate functional miRNAs.